2015
DOI: 10.12740/pp/27635
|View full text |Cite
|
Sign up to set email alerts
|

Self-mutilating behaviours in patients with mental disorders – a study on users of a social networking service

Abstract: Self-mutilations occur mostly in patients suffering from various affective disorders. In spite of obvious restrictions of this study method, a web portal may be an effective way to collect data, for it provides fully anonymous responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…With regard to related factors, although there were some disagreements about some factors, sex and the presence of mental disorder (of the individual or a family member) have been widely cited in the autores. 25,36,39 Although no consensus on the female be the higher prevalence of self-harm (35.2%), we found an interesting debate related to the first accession to self-harm and the frequency difference found between the sexes, once started the practice. In these studies, women showed greater adherence to practice, though less frequently, while the male smaller membership, but most frequência.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…With regard to related factors, although there were some disagreements about some factors, sex and the presence of mental disorder (of the individual or a family member) have been widely cited in the autores. 25,36,39 Although no consensus on the female be the higher prevalence of self-harm (35.2%), we found an interesting debate related to the first accession to self-harm and the frequency difference found between the sexes, once started the practice. In these studies, women showed greater adherence to practice, though less frequently, while the male smaller membership, but most frequência.…”
Section: Discussionmentioning
confidence: 64%
“…[32][33][34] The self-mutilation, regardless of the author's inclination to suicide and NSSI include acts of cutting, self-produced cuts, but also autoenvenenamento, self-inflicted burns, hitting (the individual himself is hit or hit against something), ischemia of body parts or whole organs , bites and autossufocamento. 35,36 These practices include changes or destruction of the body socially not form sancionada. 23,33,34,37 Some studies have suggested that there is a wide spectrum between the suicide attempt (self-mutilation with suicidal intent) and non-suicidal self-injury.…”
Section: Discussionmentioning
confidence: 99%
“…In psychiatric patients the rates are even higher: 21% for adults and 40-69% for adolescents [13,14]. The available data indicate that most cases of self-harm occur in the course of bipolar disorder and a recurrent depressive episode [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, adequate diagnosis is complicated by the fact that only a few percent of patients share their selfmutilation intention with their relatives or mental health specialists [15].…”
Section: Discussionmentioning
confidence: 99%